PEMIKIRAN PENDIDIKAN ISLAM PERSPEKTIF JALALUDDIN - Romli Romli; Abdurrahmansyah Abdurrahmansyah; Abdullah Idi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2023)
This study aims to analyze the construction of Islamic education thought in Jalaluddin's perspective and the relevance of Jalaluddin's educational thought in the constellation of modern or global education. This type of research is library research. The approach used is descriptive analytical. The primary sources used are books and information in the field related to Jalaluddin's Islamic education thought. While secondary sources are reports, books, notes that are closely related to the problem under study. Data collection methods through documentation. The data analysis technique uses document analysis method or content analysis. This study found that the thought of Islamic education in Jalaluddin's perspective includes 1) the new direction of Islamic education, education should be directed to form humans into insan kamil; 2) Islamic education thinking, one of which is the democratization of Islamic education with the ultimate goal of forming a democratic, clean, moral and moral Indonesian society and adhering to the value of civilization, 3) renewal of Islamic education, in Islamic education it is necessary to develop a dual approach strategy with the aim of combining short-term situational approaches with long-term conceptual approaches; and 4) character education, four joints of good character based on the characters of patience, self-respect, courage, and justice.